Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.4269/ajtmh.1999.61.814
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of plague associated with increased winter-spring precipitation in New Mexico.

Abstract: Abstract. Plague occurs episodically in many parts of the world, and some outbreaks appear to be related to increased abundance of rodents and other mammals that serve as hosts for vector fleas. Climate dynamics may influence the abundance of both fleas and mammals, thereby having an indirect effect on human plague incidence. An understanding of the relationship between climate and plague could be useful in predicting periods of increased risk of plague transmission. In this study, we used correlation analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
197
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(211 citation statements)
references
References 23 publications
10
197
0
1
Order By: Relevance
“…Increased plague intensity after wet years, and reduced plague intensity during and after dry years in northern China is consistent with the trophic cascade hypothesis (18,21). Abundant precipitation has been demonstrated to promote population growth of small rodents through increased food availability in many continents (25)(26)(27).…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Increased plague intensity after wet years, and reduced plague intensity during and after dry years in northern China is consistent with the trophic cascade hypothesis (18,21). Abundant precipitation has been demonstrated to promote population growth of small rodents through increased food availability in many continents (25)(26)(27).…”
Section: Discussionsupporting
confidence: 60%
“…In New Mexico, human plague cases occurred more frequently after winter and spring periods with above-average precipitation (18). Time-lagged winter-spring precipitation was also positively associated with the frequency of human plague cases in the southwestern United States (19).…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…Nonetheless, we believe such an association with agricultural intensity and plague case occurrence is biologically plausible. According to a trophic cascade hypothesis, [35][36][37] areas with increased primary production of food crops may increase the carrying capacity of rodents. Several quantitative models have demonstrated that the probability of plague epizootics, which represent periods when humans are at greatest risk for exposure to infectious fleas, 38 is dependent on reaching critical thresholds of key rodent hosts.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings corroborate those of other studies on temporal associations with human plague incidence [18][19][20] . Parmenter et al 21 found that the cyclical pattern of the annual distribution of plague cases in New Mexico (USA) was associated with fluctuations in the rodent population or in the rodents' responses to environmental variations such as food and shelter availability.…”
Section: Yearmentioning
confidence: 99%